An Observational Study of Practice Among Food Manufacturers in Defining Serving Sizes of Chocolate Confectionery Products Sold in UK Supermarkets - Simon J Howard (International Journal of Nutrition, 2016)
Objective To provide data on the consistency of recommended serving sizes of single bars and bags of chocolate confectionery products sold in UK supermarkets, in terms of weight and energy content. Methods Data were obtained from supermarket websites on the weight, calorific content and recommended serving size of all products classified as single bars or bags of chocolate confectionery products in at least two of the three supermarkets with the largest share of the grocery market in the United Kingdom. Results The number of servings per product varies from 1 to 3. Recommended serving sizes vary widely in terms of weight and energy content (ranges 18-83.4g and 88-265kcal respectively). Recommended serving sizes vary even between identical products sold in different size packages. Conclusions There is potential for consumer confusion over a reasonable serving size of chocolate products, especially in the wider nutritional context of well-described portion sizes for food categories such as fruit. Alternatively, the inconsistency may derive from a reasonable attempt to make front-of-pack labelling easy for consumers to understand by using intuitive fractions of the contents.
Keywords: Serving Sizes